Should place-based jobs policies be used to help distressed communities? - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2019)
Should policymakers seek to increase jobs in particular local labor markets? Yes, but only if these policies are well targeted and designed. Encouraging job growth in distressed places can cause persistent gains in employment-to-population ratios. But our current place-based jobs policies, under which state and local governments provide long-term tax incentives to megacorporations, are poorly targeted and designed. Such incentives are as large in nondistressed areas as in distressed areas, and they are excessively costly. What reforms are needed? First, job growth policies should target distressed areas. Second, tax incentives should be focused on high-multiplier businesses, such as high-tech firms. Third, officials can more effectively promote local job creation by relying less on tax incentives and more on public services. These include customized business services, infrastructure, land development policies, local education, and job training. The federal government can use taxes and intergovernmental grants to discourage city or state officials from giving excessive state and local incentives to the largest firms. The federal government can also provide block grants to state and local governments to provide services that promote job growth in distressed places.
Keywords: R58; R23; H73; H77; 330; distressed places; regional development policies; local labor markets